Real Time Monitoring of Groundwater Fluorescence: Principle and Applicability in Nepal - Khadka, Aakriti; Oikonomou, Christina; Paudel, Shukra Raj (Journal of the Institute of Engineering, 2020)
As Nepal sits on the Indo-Eurasian plate boundary, it is highly susceptible to catastrophic earthquakes which have been posing a grave threat to the people of the country. Even though earthquake is one of the most destructive natural phenomena, its occurrence is still unpredictable. Advance warning of disastrous earthquakes is crucial so that the damage due to it is minimal. Different changes in the properties of groundwater prior to earthquake have been detected which can give important hints. Among them, the increase in fluorescent intensity of groundwater comprises a significant earthquake precursor. The positive holes, formed due to tectonic stresses in rocks with peroxy defects, interact with groundwater modifying the fluorescence intensity of water. In this study, we investigate the effect of seismic activity on the groundwater fluorescence intensity. The necessity of this examination for the country is also demonstrated. Taking into account the large variation in the groundwater quality and types of rock in Nepal, the investigation of fluorescent intensity using fluorometer may unravel different uncertainties and limitations. The simplicity of fluorometer in installation, methodology, maintenance, and its sensitivity up to large catchment area make it suitable for such investigation. Till now, variations of the groundwater fluorescent intensity have not been deeply studied in Nepal. This is of high importance in terms of earthquake forecast considering the high seismic activity in Nepal which lies on a very seismically active zone.